PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA BAGIAN BOILER DI PABRIK SPIRITUS - , Mahdinursyah, SKM, Dr. dr. Lientje Setyawati Maurits, MS. Sp. Ok. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background :Intention to performing any behavior very determine whether the action will be performed or not by anyone because human will use basic assumption consciously by considering all available information in their environment. Therefore, there are 3 determinants of intention based on theory of planned behavior. Occupational accident and occupational related illness is the most frequent emerging impact in any industry that use boiler as their main energy source in the current time. Study Purpose : The objective was to analyze the intention of the workers at boiler unit to using PPE hence able to prevent the danger of occupational accident and occupational related illness. Study Method : This was qualitative study used phenomenology design approach and trustworthiness and for the data reliability (validity) used data triangulation method between indepth interview, workerâs medical record and field observation. Study Result : From the study that was performed was obtained that inconsistent and non continue PPE usage by the workers through the world and among others was in Indonesia and especially in Yogyakarta, the lack of emergency training and danger management at boiler unit, and also the lack of motivation to use PPE, and also the lack of anticipation to reduce the danger that probable to occurs and periodic examination and special examination that was not performed appropriately, other of that was the lack of warning board in the workroom was also occurs. Conclusion : Thus it can be concluded that the attitude to the workerâs behavior was still deficient especially at the level of subjectâs knowledge, whereas the subjective norm both of coworkers and their environment was also take not much role to used PPE and perception of the subjectâs control ability would improved after the subject suffered any illness or occupational accident had occurs.